Viable ectopic pregnancy with hemoperitoneum - Obiozor CG; Obiozor AA (Ibom Medical Journal)
Pregnancy is said to be ectopic when it occurs outside the uterus, most commonly in the fallopian tube. There is high index of suspicion when a pregnant woman experiences any of these symptoms in the first trimester: vaginal bleeding, lower abdominal pain, and amenorrhea. An elevated BhCG level above (2000 mIU/ml) with an empty uterus on a transvaginal ultrasound is necessary for confirming ectopic pregnancy diagnosis. Ectopic pregnancy can be managed medically with methotrexate or surgically via laparoscopy or laparotomy depending on the hemodynamic stability of the patient and the size of the ectopic mass. We present a case of a left-sided viable ectopic pregnancy with massive hemoperitoneum in a 31-year-old primigravid female, who presented to a peripheral radiological centre in Umuahia Abia state with history of amenorrhea for two months severe abdominal pain and signs of hypovolemic shock. The patient was scanned trans-abdominally and findings revealed an empty uterine cavity and a live11 weeks fetus (measured by CRL), The fetus was seen within a gestational sac in the left side of the abdominal cavity floating in a free fluid in keeping with ruptured tubal ectopic pregnancy of 11wks duration. The patient underwent urgent exploratory laparotomy which revealed a ruptured left tubal ectopic pregnancy with significant intra-abdominal haemorrhage. Surgical intervention was successfully performed, culminating in the removal of the ectopic pregnancy, salpingectomy and hemostasis of the bleeding vessels. The patient recovered well postoperatively and was discharged with appropriate follow-up care. This case highlights the importance of early recognition, radiological evaluation and prompt management of ectopic pregnancies to prevent life-threatening complications.